Detection of antileishmanial antibodies in blood sampled from blood bank donors in Istanbul - Ates, Sezen Canim; Bagirova, Malahat; Allahverdiyev, Adil M.; Baydar, Serap Yesilkir; Koc, Rabia Cakir; Elcicek, Serhat; Abamor, Emrah Sefik; Oztel, Olga Nehir (FUTURE MEDICINE LTD, 2012)
Aims: According to the WHO, only 5-20% of the total cases of leishmaniasis are symptomatic leishmaniasis; the other cases are identified as asymptomatic leishmaniasis. In recent studies, it has been demonstrated that donor blood plays an important role in the epidemiology of asymptomatic leishmaniasis. However, the number of the studies on this subject is still insufficient. Additionally, donor blood samples obtained from Istanbul, which is the biggest metropolitan area in Turkey, have not been investigated with regard to Leishmania. Moreover, there is no information about the sensitivity of noninvasive serological methods that are used in the detection of leishmaniasis donor blood samples. Accordingly, this study aimed to investigate the presence of antileishmanial antibodies in blood samples obtained from blood bank donors in Istanbul, by using different serologic methods, and to determine the most sensitive detection method. Materials & methods: Blood samples were taken from 188 healthy blood bank donors to the Capa Turkish Red Crescent Blood Bank (Istanbul, Turkey), and the presence of antileishmanial antibodies was measured by indirect immunofluorescent antibody test (IFAT), ELISA, immunochromatographic dipstick rapid test, and western blot (WB). Results: Antileishmanial antibodies were determined in 12 out of 188 samples by IFAT (6.4%), and six out of these 12 donors were found to be positive at diagnostic titer 1:128 (3.2%). One hundred and eighty eight samples were investigated by ELISA and one (0.5%) of them gave a positive result. None of 188 samples provided a positive result by immunochromatographic test. WB applied to the 12 seroreactive donors showed that three out of 12 donors were positive. Conclusion: In this study, the presence of antileishmanial antibodies in blood samples of blood bank donors from Istanbul has been demonstrated by using feasible and low-cost serological methods. Additionally, in comparison with other simple and low-cost detection methods, WB was used for confirmation. IFAT has a higher sensitivity and therefore may be preferred as a prescreening method in endemic or nonendemic areas.
Keywords: blood donors; ELISA; immunochromatographic dipstick rapid test; immunofluorescence antibody test; leishmaniasis; western blot; VISCERAL LEISHMANIASIS; CANINE LEISHMANIASIS; BALEARIC-ISLANDS; DIAGNOSTIC-TESTS; KALA-AZAR; INFANTUM; TRANSMISSION; TRANSFUSION; INFECTION; DONOVANI; Microbiology